Code-Switching Found in Tomohiro Yamashita's YouTube Channel - Novelia, Novelia; Panggabean, Himpun; Silalahi, Charles David Marudut (CV. Eduartpia Publisher, 2025)
People nowadays often communicate using multiple languages. When the speaker uses two or more languages, regularly switching and blending them when communicating is known as code-switching. This research aims to find out and show readers the types of code-switching and why code-switching is used in Tomohiro Yamashita's YouTube channel vlogs. In this research, the writer used the descriptive qualitative research design. The theories proposed by (Poplack, 1980) were used to classify the types of code-switching and theories by (Hoffmann, 1991) were used to find out the reasons of using code-switching. In the 1st video, there were 66 data of code-switching found with 50 (75.76%) inter-sentential, 9 (13.64%) intra-sentential, and 7 (10.6%) tag-switching. In the 2nd video, there were 84 data of code-switching found with 57 (67.86%) inter-sentential, 25 (29.76%) intra-sentential, and 2 (2.38%) tag-switching. In the 3rd video, there were 29 data of code-switching found with 17 (58.62%) inter-sentential, 11 (37.93%) intra-sentential, and 1 (3.45%) tag-switching. In the 4th video, there were 23 data of code-switching found with 12 (52.17%) inter-sentential, 11 (47.83%) intra-sentential, and 0 tag-switching. In the 5th video, there were 7 data of code-switching with 4 (57.14%) inter-sentential, 3 (42.86%) intra-sentential, and 0 tag-switching. Besides that, the writer also found several reasons for using code-switching in Tomohiro Yamashita's YouTube channel vlogs, including, talking about particular topic, be emphatic about something, interjection, repetition used for clarification, and intention of clarifying the speech content for interlocutor.